Effect of graphite addition on microstructure and properties of TiC–Ti5Si3–SiC composite coatings reacted from Ti–SiC-graphite powders - Yufeng Li; Yehui Bi; Yue Xing; Jining He; Yanfang Qin; Hongjian Zhao (Journal of Materials Research and Technology, 2023)
A TiC–Ti5Si3–SiC composite coating was prepared using atmospheric plasma spraying by in-situ reaction of raw agglomerated Ti–SiC-graphite powders. The effect of graphite content on the reaction mechanism, microstructure, and properties of plasma sprayed TiC–Ti5Si3–SiC coatings was studied. The results indicated that, with the increase of graphite content, Ti and C preferentially reacted and the reaction feasibility between Ti and SiC reduced. The content of TiC in the reaction products and unreacted SiC increased, while the content of Ti5Si3 decreased. Among them, the TiC–Ti5Si3–SiC coating prepared using Ti–SiC-graphite powders with a molar ratio of 3:1:1 exhibits excellent comprehensive properties, dense microstructure (porosity: 11.76 %), highest hardness (1132 HV0.2), high bonding strength (scratch critical load: ∼44 N), and optimal wear resistance with a wear loss weight of ∼5 × 10 −4 g.